Assessing the role of AI technology in mitigating the equity gap in educational access in Zimbabwe: Barriers and implications (Journal of Applied Learning and Teaching, 2025)
This study investigates the role of artificial intelligence (AI) technology in mitigating the equity gap in educational access in Zimbabwe. By exploring the potential benefits, limitations, and best practices of using AI technology, this research contributes to a deeper understanding of how AI can address the complex issue of equity in higher education. Data was collected from lecturers and students through interviews, revealing that AI technology offers affordable, independent, personalized learning experiences and student support, enabling vulnerable learners to access educational resources. However, challenges such as the high cost of premium AI platforms, internet accessibility issues, and potential social skills deficits were identified as limitations to widespread implementation. The study recommends developing AI policies, university subscriptions to premium AI technologies, and the rollout of AI chatbots to ensure equitable and accessible learning opportunities for all students. This research sheds light on the importance of leveraging AI technology to promote inclusive education systems and close the equity gap in educational access, offering valuable insights for educational institutions in Zimbabwe and beyond.